Research Collaboration and Impact of Central Agricultural University and Manipur University India: A Scopus Based Study - Hazarika, Rima; Sudhier, K G (DESIDOC Journal of Library & Information Technology, 2025)
The paper explores the research impact and collaboration of Central Agricultural University (CAU) and Manipur University (MU), India, between 2013 and 2022. A bibliometric analysis of 1,932 publications and 23,519 citations extracted from the Scopus database reveals a significant increase in publications. Notably, 77.64 % of these papers resulted from national collaborations, while 22.41 % had international, particularly with the United States, the United Kingdom, and South Korea. The analysis of co-authorship patterns indicates a decline in single and two-authored papers, while multi-authored papers have increased significantly. The study highlights the rapid growth of collaboration networks, with CAU, Imphal leading in national collaborations across 61 countries. These findings provide that both CAU and MU have significantly expanded their research networks, resulting in improved research output and citation impact.